Osteoporosis screening by measuring calcaneus bone mineral density through quantitative ultrasonography in healthcare workers - Sherazi, Noreen (Journal of the Pakistan Medical Association, 2026)
Objectives: To evaluate the frequency of low bone mineral density among healthcare workers, identify gender and age-related trends, and assess the feasibility of implementing routine screening programmes for early detection and prevention of bone health deterioration. Method: The analytical, cross-sectional study was conducted at the Section of Biochemistry, Department of Pathology and Laboratory Services, National Institute of Cardiovascular Diseases, Karachi, during a one-day screening camp on June 1, 2023, and comprised hospital staff members of either gender aged 20-70 years who were apparently healthy. Bone mineral density was assessed using a portable stand-alone quantitative ultrasound bone densitometer. The T-scores were interpreted as per World Health Organisation guidelines. Data was compared among normal, osteopenic and osteoporotic groups. Data was analysed using SPSS 29. Results: Of the 200 subjects, 123(61.5%) were male and 77(38.5%) were female. The mean age was 38.8±9.6 years. Normal bone health was found in 23(11.5%) subjects, osteopenia in 100(50%) and osteoporosis in 77(38.5%). The average T-score was -2.16±0.8. Females exhibited a significantly higher prevalence of osteoporosis 41(53.25%), while males were more likely to have osteopenia 72(58.54%). Those aged between 25-45 years (n=149) exhibited osteoporosis (38.9%) and osteopenia (51%). T-scores and Z-scores showed significant difference across the three groups (p 0.001). Conclusion: A high prevalence of low bone mineral density among hospital staff was noted, highlighting the need for workplace-based osteoporosis prevention programmes. Key Words: Osteoporosis, Bone density, Ultrasonography, T-score, Healthcare personnel.